Study of the peri-operative mortality in trochanteric fractures in elderly patients (60 years and above) visiting department of orthopedics at Dr. RPGMC Tanda - Singh, Sarvesh Kumar; Awasthi, Bhanu; Kumar, Devinder; Rana, Sunil; Singh, Atul; Dua, Sunny (International Journal of Research in Orthopaedics, 2021)
Background: In elderly, trochanteric fractures are frequent and typically result from mild to moderate trauma in osteoporotic bones while in young adults these fractures are generally due to high energy trauma such as road side accidents. Methods: The present study was conducted in elderly patients with trochanteric fractures (age 60 years and above) presenting to the department of orthopedics, Dr. RPGMC Kangra at Tanda. All cases presenting to the department and fulfilling the inclusion criteria were studied for three months period from the day of surgery. All cases fulfilling the inclusion criteria who were operated over the period of one year from the date of start of study were included. Results: Our study observed that out of 176 patients, 10.23% (n=18/176) patients could not survive within 90 days of surgery while 89.8% (n=158/176) patients survived. Perioperative mortality was 10.23%. Conclusions: In our study, peri-operative mortality is lower than reported earlier. We also found that perioperative mortality was influenced by older age.